Absence of Organ Specific Toxicity in Rats Treated with Tonica, an Aqueous Herbal Haematinic Preparation - Martey, O.N.K.; Armah, G.E.; Okine, L.K. (African Journal of Traditional, Complement and Alternative Medicines, 2010)
The sub-chronic toxicity of Tonica, an aqueous herbal haematinic prepared from the stem barks of Khaya senegalensis, Mitragyna stipulosa and Kigelia africana, was investigated in male Sprague-Dawley rats at 28, 280 and 560 mg kg−1 day−1, representing the normal human dose, 10x and 20x that dose, respectively for 6 weeks. The growth rate of animals over the period of treatment and certain serum biochemical and haematological indices as well as urinalysis and weight of selected organs at termination, were determined. Results show that the extract did not affect the weight gain of the animals with time or the mean wet weights of selected organs. Although there were slight but insignificant (p>0.05) elevations in WBC (16–27%) and PLT (8–11%) counts in Tonica-treated animals compared to controls at 10x and 20x the normal dose, most serum biochemical, haematological and urinalysis data indicated no significant differences (p>0.05) between tests and control rats. There were also no changes in the morphology of liver, kidney, lung and heart tissues as a result of Tonica treatment. These findings suggest that Tonica is safe at the dosage regimens administered to the animals in this study, and there appears to be no overt organ specific toxicity associated with it.
Keywords: Khaya senegalensis; Mitragyna stipulosa; Kigelia africana; sub-chronic; toxicity